2016
DOI: 10.1002/art.39742
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Causes of Stillbirths in Women With Systemic Lupus Erythematosus

Abstract: Objective. There are few precise or recent estimates of the risk or causes of stillbirths in women with systemic lupus erythematosus (SLE). Thus, we undertook the present study to examine causes of stillbirths in mothers with SLE versus those without SLE.Methods. The Offspring of SLE Mothers Registry (OSLER) is a large population-based cohort, identified through Quebec's health care databases , including all women who had ‡1 hospitalization for delivery after SLE diagnosis, and a randomly selected control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…2,[5][6][7][8][9][10][11] SLE mainly affects young women of childbearing age, and adverse pregnancy outcomes (APOs), such as abortion, premature birth, stillbirth and termination, occur more often in women with SLE than in healthy women. 12,13 Some reports have shown disease activity, APS and GC usage as predictors for APOs. 14,15 A previous study showed that the pregnancy itself did not relate to chronic damage at the first visit after the deliveries, but chronic damage in patients with longer observation was not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7][8][9][10][11] SLE mainly affects young women of childbearing age, and adverse pregnancy outcomes (APOs), such as abortion, premature birth, stillbirth and termination, occur more often in women with SLE than in healthy women. 12,13 Some reports have shown disease activity, APS and GC usage as predictors for APOs. 14,15 A previous study showed that the pregnancy itself did not relate to chronic damage at the first visit after the deliveries, but chronic damage in patients with longer observation was not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Intrauterine deaths in women with SLE occur earlier than in controls (median 29 weeks in patients with SLE versus 35 weeks in healthy patients) and are more frequent in cases of severe FGR (below the 3 rd percentile) or altered flow at foetal Doppler velocimetry (43,44). In this study, foetal deaths in patients with FGR were even earlier (26 weeks), with all SGA stillborn below the 3 rd percentile and 75% of them presented abnormalities in Doppler velocimetry.…”
Section: Discussionmentioning
confidence: 47%
“…Previous reports reveal that the APOs in SLE patients exceed that of the general population: SLE flare during pregnancy: 21.4%–64%, gestational hypertension: 0.99%–45%, gestational diabetes mellitus: 0%–11%, preeclampsia: 5.4%–20.2%, HELLP syndrome: 0.3%–0.66%, preterm birth: 9%–56%, spontaneous abortion: 0.4%–25%, SGA: 10%–28.5%, Apgar score less than 7 at 1 min: 1%–18% 3,4,8,19–26,2849 We summarized the frequency of each APO in Table 5.…”
Section: Discussionmentioning
confidence: 97%